Terahertz lattice enhanced quasi-anapole immunosensor assisted by protein antibody and AuNPs - Luo, Chengcheng (2024)
Terahertz (THz) metasurface immunosensor has the characteristics of label-free detection, good biocompatibility and high specificity because the antibody-modified of biomarkers has the ability to specifically recognize corresponding biomarkers and increase the detection sensitivity to the concentration of the recognized antigen. The limit of detection (LoD) of THz metasurface immunosensor is highly dependent on resonant field enhancement of metasurface. The anapole mode shows a radiationless state with nontrivial oscillating current configuration. To observe such mode in farfield, in this work, the concept of quasi-anapole (QA) mode is presented which is induced when the electric and toroidal dipoles with identical intensity radiate in antiphase on the metasurface with the unit cell of two split ring resonators (SRRs) on both sides of the central cut-wire. In addition, by coupling the first-order lattice mode to the QA mode, lattice-enhanced QA mode (LQA) was investigated and observed to further enhance field confinement and decrease radiative loss. As a practical application, immunosensor was designed and fabricated by functionalized gold nanoparticles conjugated with the specific monoclonal antibody onto the LQA metasurface to detect the cell concentration of SARS-CoV-2 spike protein. The experimental results indicate that the response of LQA immunosensor depends heavily on the concentration of the Anti-S modified on its surface. When the concentration of Anti-S is 50 pg/ml, the LoD reaches to 3 pg/ml (39 fmol). Such THz LQA immunosensor also shows good specific identification and validates its effectiveness in biomedical sensing.